The unconstitutional detention for more than 48 hours without the request for pretrial detention - Solís Canchari, José Carmelo (2018)
In cases of flagrancy, the Constitution determines a maximum period of detention of 48 hours; the Code of Criminal Procedure authorizes an extra 48 hours for the development of the hearing of the immediate process. In this article, we analyze whether it is constitutional or not to detain the accused for 96 hours (four days) in order to discuss the proceeding of the immediate process.